Collaborative practice within the practice teacher-student relationship in social work field education: Reflections, learning and possibilities - Bolger, Ellen; Crosse, Nuala (The Journal of Practice Teaching and Learning, 2023)
This article will present a reflection on the benefits of a collaborative approach in the field of social work practice education and learning. It will specifically outline how collaborative practice, centered around a practice teacher and their student, was developed in a hospital neurorehabilitation setting. This will be demonstrated via the innovations which took place in establishing a peer support group for a cohort of patients under the age of 65. We will discuss with the reader, our framework which was developed with the intention of promoting an investment by practice teachers, students, field agencies and college educators in taking part in collaborative practice within the education environment. We will outline and reflect on the 3 main principles of our framework for collaborative practice within the realm of social work. These include: 1) Individual Traits, 2) Reflective Practice and 3) Learning and Professional Development. This article will highlight the benefits of embracing a collaborative approach in practice education by focusing on the principles above, within an interdisciplinary work setting.